Financial Target, Nature of Industry, Change in Auditors, Change in Directors regarding Financial Fraud and Audit Quality as Moderating Variables - Agnes K. B. Mudamakin; Eugenia H. P. Tanan; Dimas Julian Huan (Borong Newinera Publisher, 2026)
Audits are conducted to ensure that the information in financial statements is accurate and to provide users with confidence in management's accountability. However, financial statements still contain errors due to incomplete or biased reporting, or fraud. The 2022 ACFE results show that Indonesia ranks fourth among the four most fraudulent countries in the Asia-Pacific. In Indonesia, there were 23 cases of fraud, with 6.7 percent of these cases involving financial statement fraud. This indicates that management continues to commit fraud in financial reporting. Therefore, the purpose of this study is to examine the influence of financial targets, industry nature, changes in directors, and auditor changes on financial fraud. This study will utilize data from 13 state-owned enterprises listed on the Indonesia Stock Exchange. The results show that the moderating effect of audit quality weakens the influence of financial targets, industry nature, changes in directors, and auditor changes on financial fraud.